Government Ownership, International Operations ,Board Independence and Environmental Disclosure: Evidence from Asiaâ€“Pacific - Ifada, Luluk Muhimatul; Indriastuti, Maya (Jurnal Dinamika Akuntansi, 2021)
Purpose: This study examines the relationship between government ownership, international operations, and board independence as an independent variable on environmental disclosure in public companies in Asia Pacific emerging markets.Method: This study used a purposive sampling method for 53 companies from 76 emerging market public companies in the Asia Pacific with an environmental disclosure score in 2018, with cross-section data. This study used secondary data that were processed by the Ordinary Least Square (OLS) method as the main research method, andÂ  showed a significant positive relationship.Findings: Government ownership, international operations, board independence, have a positive effect on environmental disclosure. Government ownership has a positive effect on environmental disclosure, meaning that companies with government ownership can be emphasized to comply with environmental regulations with better environmental disclosure. International operations positively affect environmental disclosure, meaning that companies operating internationally are more proactive in social and environmental responsibility, which can increase the interest of companies to make environmental disclosures. Board independence positively affects environmental disclosure, indicating that board independence allows a focus on long-term environmental investment through corporate environmental disclosure.Novelty: The originality of this study examines emerging market public companies throughout developing countries in the Asia Pacific. This is to capture the context of environmental disclosure among developing countries.